Three-dimensional Hemifacial Microsomia Classification with New Subtypes Based on the Pruzansky and Kaban Classification - Reiko Shibazaki-Yorozuya, DDS, PhD; Akira Yamada, MD, FACS, PhD; Ryo Sasaki, DDS, PhD, FIBCSOMS; Yorikatsu Watanabe, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2024)
Background:. Various classifications of hemifacial microsomia (HFM) have been described previously. Although some of these classifications are used widely, others use external outlines of reference organs, even in three-dimensional (3D) images. The purpose of this study was to investigate the 3D characteristics of the mandibular condyle in HFM and to update the Pruzansky and Kaban classification as a 3D classification. Methods:. Fifty-three patients with HFM were classified according to the Pruzansky and Kaban classification (type I, IIA, IIB, and III) using computed tomographic scan images. 3D images of the mandible were isolated, and the 3D characteristics were observed; furthermore, the angle of inclination of the mandibular condyle was measured in 3D. Results:. Subtypes of retroflexed mandibular condyle in 3D were observed in the Pruzansky and Kaban classification type IIA and IIB, termed as type IIAβ (33.3% in type IIA) and type IIBβ (100% in type IIB). Although some differences were observed in the inclination of the mandibular condyle between the control and the affected sides in type I and IIAα, multiple differences were observed in type IIAβ and IIBβ. Conclusions:. To the best of our knowledge, this is the first report that identified the retroflexed mandibular condyle as subtypes type IIAβ and IIBβ. Notably, this could not be identified in the two-dimensional images (lateral cephalogram) yet. We proposed to update the Pruzansky and Kaban classification as a 3D classification with a new 3D subtype. The angle of the retroflexed mandibular condyle may predict mandibular growth in HFM.